2018
DOI: 10.1117/1.jbo.23.7.075005
|View full text |Cite
|
Sign up to set email alerts
|

Investigating optical path and differential pathlength factor in reflectance photoplethysmography for the assessment of perfusion

Abstract: Photoplethysmography (PPG) is an optical noninvasive technique with the potential for assessing tissue perfusion. The relative time-change in the concentration of oxyhemoglobin and deoxyhemoglobin in the blood can be derived from DC part of the PPG signal. However, the absolute concentration cannot be determined due to the inadequate data on PPG optical paths. The optical path and differential pathlength factor (DPF) for PPG at red (660 nm) and infrared (880 nm) wavelengths were investigated using a heterogene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
27
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 26 publications
(33 citation statements)
references
References 49 publications
2
27
0
Order By: Relevance
“…Although there are some fluctuations in the curves of f blood and StO 2 which are likely caused by motion artifacts, f blood and StO 2 during the occlusions apparently deviated from the baseline and the deviations were much larger than standard deviations during the baselines. The decreases in StO2 during both occlusions are similar to results reported in previous studies [33,[37][38][39][40], and are expected because tissue consumes oxygen and no oxygenated blood is supplied under the occlusions. We observed that f blood decreased slightly during both arterial and venous occlusions, which are not in agreement with trends often reported [33,[35][36][37]40].…”
Section: In-vivo Cuff Occlusion Experiments Resultssupporting
confidence: 89%
See 2 more Smart Citations
“…Although there are some fluctuations in the curves of f blood and StO 2 which are likely caused by motion artifacts, f blood and StO 2 during the occlusions apparently deviated from the baseline and the deviations were much larger than standard deviations during the baselines. The decreases in StO2 during both occlusions are similar to results reported in previous studies [33,[37][38][39][40], and are expected because tissue consumes oxygen and no oxygenated blood is supplied under the occlusions. We observed that f blood decreased slightly during both arterial and venous occlusions, which are not in agreement with trends often reported [33,[35][36][37]40].…”
Section: In-vivo Cuff Occlusion Experiments Resultssupporting
confidence: 89%
“…The decreases in StO2 during both occlusions are similar to results reported in previous studies [33,[37][38][39][40], and are expected because tissue consumes oxygen and no oxygenated blood is supplied under the occlusions. We observed that f blood decreased slightly during both arterial and venous occlusions, which are not in agreement with trends often reported [33,[35][36][37]40]. This discrepancy might be partly, due to the short SDS used in the current SRDRS system that is more sensitive to the micro-circulation in the superficial dermis.…”
Section: In-vivo Cuff Occlusion Experiments Resultssupporting
confidence: 89%
See 1 more Smart Citation
“…Chatterjee et al [12] utilise Monte Carlo simulations to examine the distribution of photons within perfused skin. They concluded that the Differential Pathlength Factor (DPF) is dependent on wavelength and source-detector separations contrary to prior assumptions [13]. Although such studies are producing interesting results, a common limitation is the static nature of the simulation design where arterial pulsations are ignored.…”
Section: Introductionmentioning
confidence: 99%
“…A number of research works have been carried out previously to evaluate the dependence of DPF on tissue location, sensor geometry, optical wavelength and age [3], [4], [5], [6]. Recent studies have also identified a variation in DPF between larger and smaller source-detector separations, typically used in noninvasive applications such as Near-Infrared Spectroscopy (NIRS) and Photoplethysmography (PPG), respectively [7]. The importance of an accurate DPF assessment for a specific application has been demonstrated in previous works that have shown significant cross-talk errors in the measured concentration of oxyhaemoglobin and deoxyhaemoglobin for an inaccuracy in the DPF value [9], [10], [11].…”
Section: Introductionmentioning
confidence: 99%